Determination of nanogram quantities of osmium-labeled single stranded DNA by differential pulse stripping voltammetry - Kizek, René; Havran, Ludek; Fojta, Miroslav; Palecek, Emil (Bioelectrochemistry (Amsterdam, Netherlands), 2002)
Earlier, we showed that using differential pulse cathodic stripping voltammetry with hanging mercury drop electrode (HMDE), single-stranded (ss) DNA modified with osmium tetroxide, pyridine reagent (Os,py) can be determined at concentrations down to about 10-5 ng/ml. Here, we show that by exchanging Os,py for osmium tetroxide, 2,2'-bipyridine (Os,bipy) and decreasing the pH of the background electrolyte from neutrality to about pH 4, ssDNA can be determined at concentrations lower by one order of magnitude. Determination of DNA at such low concentrations may find use in various areas of molecular biology and in biotechnologies, including the development of DNA sensors.
Keywords: Osmium; jednovláknová DNA; DNA, Single-Stranded; osmium; Electrochemistry; elektrochemie